Output Efficiency and Liquidity Risk of Islamic Banks - Nurul Nadiyah Hashim; Aisyah Abdul-Rahman; Syajarul Imna Mohd Amin (Türkiye İslam İktisadı Dergisi)
This study analysed the relation between efficiency and liquidity risk of worldwide Islamic banks from 1986 to 2015. Bank efficiency was estimated based on output efficiency by using stochastic frontier approach (SFA), while liquidity was calculated by using liquidity ratio (LR) and net stable funding ratio (NSFR) to examine the short-term and long-term liquidity risks. A twostage analysis was conducted: 1) output distance function was used to estimate the scores of bank efficiency, and 2) system generalised method of moments (GMM) was employed to investigate the relation between output efficiency and liquidity. Finding showed that high output efficient banks had an inverse relation with LR, but a positive relation with NSFR. This implied that increasing output efficiency only jeopardised liquidity in the short-term, but increased liquidity in the long-term, conjecturing that being efficient is beneficial in the long-term period. Regulators and bank executives should consider the diverse effect of bank efficiency with the aim of having a holistic liquidity risk management framework.